2018
DOI: 10.30880/jst.2018.10.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Diversity of Pestalotiopsis, Neopestalotiopsis and Pseudopestalotiopsis Species from Four Host Plants in Sarawak, Borneo Island (Malaysia)

Abstract: Until recently, Pestalotiopsis species have been identified based on host relationship and conidial dimensions. Pestalotiopsis species occur as endophytes, saprobes and also pathogens of many plant hosts. This study used molecular phylogenetic relationships based on ITS sequence data to identify Pestalotiopsis, Neopestalotiopsis and Pseudopestalotiopsis species in addition to their conidial pigmentation from four host plants namely Macaranga triloba, Macaranga sp., Shorea macrophylla and Syzygium sp. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Pathogenicity tests revealed that all isolates of F. solani and F. (Lateef et al, 2018;Maharachchikumbura et al, 2014). In this study, the isolates obtained were suspected to be Neopestalotiopsis sp.…”
Section: Pathogenicity Testmentioning
confidence: 66%
See 1 more Smart Citation
“…Pathogenicity tests revealed that all isolates of F. solani and F. (Lateef et al, 2018;Maharachchikumbura et al, 2014). In this study, the isolates obtained were suspected to be Neopestalotiopsis sp.…”
Section: Pathogenicity Testmentioning
confidence: 66%
“…Furthermore, 10 isolates of N. clavispora were obtained in this study from infected leaves of T. cacao in Malaysia. The Pestalotiopsis clade has been redefined into two clades with two new genera, namely Pseudopestalotiopsis and Neopestalotiopsis (Lateef et al., 2018; Maharachchikumbura et al., 2014). The genus Pestalotiopsis produces lightly pigmented concolorous median cells, Neopestalotiopsis produces versicolor median cells and Pseudopestalotiopsis produces darkly coloured concolorous median cells (Lateef et al., 2018; Maharachchikumbura et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Along with other species of Pestalotiopsis , P. disseminata is frequently isolated as an endophyte from healthy plant tissues (e.g. Lateef et al., 2018 ; Liu et al., 2012 ; Tejesvi et al., 2009 ; Wei et al., 2007 ). As many other endophytic species, it may remain dormant until the plant is stressed, and then displays a pathogenic behaviour (Maharachchikumbura et al., 2011 ).…”
Section: Pest Categorisationmentioning
confidence: 99%
“…(Crous et al., 2006 ) and Morus alba (Philip, 1995 ). More recently, P. disseminata has attracted the interest of many scientists due to its wide array of bioactive secondary metabolites (Deyrup et al., 2006 ; Hwang et al., 2015 ; Hwang et al., 2016 ) and, consequently, this species has been repeatedly isolated from wild species along with other endophytic fungi (Lateef et al., 2018 ; Liu et al., 2012 ; Tejesvi et al., 2009 ; Wei et al., 2007 ).…”
Section: Pest Categorisationmentioning
confidence: 99%
“…( 1989 ), cited by CABI online Shorea macrophylla Dipterocarpaceae Light red meranti Lateef et al. ( 2018 ) S. robuta Dipterocarpaceae Sal tree Harsh et al. ( 1989 ), cited by CABI online Terminalia morobensis Combretaceae Deshmukh et al.…”
mentioning
confidence: 99%